The Success Factors of Tourists’ Intention to Visit Cirebon Town, West Java, Indonesia - Wibowo, Riyanto; Wibowo, Toni Ari; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
In the business of tourism, factors of product quality and service quality, could affect the perceptions and satisfaction of tourists during the tour could affect the desire of tourists to return to the city of Cirebon. Domestic tourists visiting the city of Cirebon are varied and contributed to the development of tourism in the city of Cirebon. This research identifies the critical success factors of the tourist to visit the Cirebon Town as a city of their destination for vacation. The word of mouth, perception and the environment are vital for the growth of the tourism business and this research found that these determinants contributes to the successfulness of the tourism industry in the Cirebon. The travel agencies in Cirebon Town must engage in promotional activities as well as their service quality in order to enhance their core-competencies by way of developing synergy among their employees and achieve better performance. Thus, this research found that perception and the environment are the critical success factors for tourist to perform visitation at the Cirebon Town, Indonesia. The word of mouth (WOM) has been found as not significant and does not affect the intention of the tourist to visit the city of Cirebon.